Nuevo paradigma institucional de la SUNAT y su efecto en la calidad del servicio brindado al contribuyente de Iquitos 2022 - Armas Garcia, Sandro Lenin (2024)
The objective of the research was to determine the effect of the implementation of the new institutional paradigm of SUNAT on the quality of service provided to the taxpayer of the city of Iquitos, 2022, where a quantitative study and pre experimental design have been used. Taking as a population 853 taxpayers to whom a questionnaire was applied to collect information. Meanwhile, it was obtained as results that the institutional paradigm is qualified as regular by 23%. Regarding the level of quality of service provided to the taxpayer before the implementation of the new institutional paradigm in the Sunat Iquitos headquarters, it is qualified as regular by 27%. While the level of quality of service provided to the taxpayer after the implementation of the new institutional paradigm in the Sunat is qualified as good by 51%; therefore, the implementation of SUNAT's new institutional paradigm has had a positive effect on the quality of service, contrasted by a significance of 0.000.